A Molecular Interaction Map of Klebsiella pneumoniae and Its Human Host Reveals Potential Mechanisms of Host Cell Subversion - Saha, Deeya; Kundu, Sudip (Frontiers in Microbiology, 2021)
Klebsiella pneumoniae is a leading cause of pneumonia and septicaemia across the world. The rapid emergence of multi-drug resistant K. pneumoniae strains necessitates the discovery of effective drugs against this notorious pathogen. However, there is a dearth of knowledge on the mechanisms by which this deadly pathogen subverts host cellular machinery. To fill this knowledge gap, our study attempts to identify the potential mechanisms of host cell subversion by building a K. pneumoniae-Human interactome based on rigorous computational methodology. The putative host targets inferred from the predicted interactome were found to be functionally enriched in the host’s immune surveillance system and allied functions like apoptosis, hypoxia etc. A multifunctionality based scoring system revealed P53 as the most multifunctional protein amongst host targets accompanied by HIF1A and STAT1. Moreover, mining of host protein-protein interaction network revealed host targets interact amongst themselves to form a network (TTPPI), where P53 and CDC5L occupy a central position. The TTPPI is composed of several inter complex interactions which indicate that K. pneumoniae might disrupt functional coordination between these protein complexes through targeting of P53 and CDC5L. Furthermore, we identified four pivotal K. pneumoniae targeted transcription factors that are part of TTPPI and are involved in generating host’s transcriptional response to K. pneumoniae mediated sepsis. In a nutshell, our study identifies some of the pivotal molecular targets of K. pneumoniae which primarily correlate to the physiological response of host during K. pneumoniae mediated sepsis.